The Correlation Between Organophosphate Pesticide Exposure and Incidence of Prostate Cancer: A Systematic Review - Octavia, Aulia Mega Nur; Wisudanti, Desie Dwi; Wulandari, Pipiet (http://dharmais.co.id/, 2024)
Background: Organophosphate is a type of pesticide that is widely used. However, organophosphates are a group of highly toxic chemicals. The World Health Organization (WHO) estimates that nearly 3 million individuals experience organophosphate poisoning annually. One of the cancers that can develop due to exposure to organophosphate pesticides is prostate cancer. Prostate cancer is the second most prevalent cancer among men. In Indonesia, new cases of prostate cancer reached 13.563, or 7.4% of all new cancer cases in men. This study aims to determine the correlation between organophosphate exposure and the incidence of prostate cancer.Methods: This study is a research with a systematic review design. The data in this study is secondary data obtained from research articles using SPICE criteria. Pubmed, Science Direct, Springer, and Google Scholar are the databases used. The used articles were articles published between 2012 and 2022. Critical assessment was carried out using the NewcastleOttawa Quality Assessment Scale (NOS) questionnaire.Results: A total of 2.149 articles were obtained, with a range of research years from 2012 to 2022. Then a duplication selection process was carried out, free and fulltext selection. This article used the NewcastleOttawa Quality Assessment Scale questionnaire to select eligibility, so 5 articles were obtained. Among all the articles that underwent critical evaluation, it was reported that a relationship exists between organophosphate exposure and the incidence of prostate cancer among farmers. Conclusions: The evidence of this reviewed study suggests a possible association between the incidence of prostate cancer and exposure to organophosphate pesticides.